distal antenna and distal antenna-related function in the retinal determination network during eye development in Drosophila. - Curtiss, J.; Burnett, M.; Mlodzik, M. (Developmental Biology, 2007)
Drosophila eye specification occurs through the activity of the retinal determination (RD) network, which includes the Eyeless (Ey), Eyes absent (Eya), Sine oculis (So) and Dachshund (Dac) transcription factors. Based on their abilities to transform antennal precursors towards an eye fate, the distal antenna (dan) and distal antenna-related (danr) genes encode two new RD factors. Dan and Danr are probable transcription factors localized in nuclei of eye precursors and differentiating eye tissue. Loss-of-function single and double dan/danr mutants have small, rough eyes, indicating a requirement for wild-type eye development. In addition, dan and danr participate in the transcriptional hierarchy that controls expression of RD genes, and Dan and Danr interact physically and genetically with Ey and Dac. Eye specification culminates in differentiation of ommatidia through the activities of the proneural gene atonal (ato) in the founding R8 photoreceptor and Egfr signaling in additional photoreceptors. Danr expression overlaps with Ato during R8 specification, and Dan and Danr regulate Ato expression and are required for normal R8 induction and differentiation. These data demonstrate a role for Dan and Danr in eye development and provide a link between eye specification and differentiation.